Kompetensi Ilokusioner dan Literasi Visual sebagai Determinan Efektivitas Komunikasi dalam Praktik Vibecoding - Abdul Kholik; Hilwi Hanin; Diaz Wafi Raditya; Aliyyah Naurah Azka (Jurnal Multidisiplin Indonesia, 2026)
The development of generative Artificial Intelligence (AI) has given rise to a new programming phenomenon known as vibecoding, in which users employ natural language instructions to generate software code through AI systems. This phenomenon expands opportunities for individuals without technical programming backgrounds to participate in software development processes. This study aims to explore how non-programmers experience prompt construction as a form of communication with AI and to examine the role of visual communication competence in supporting effective interaction. Using an Interpretative Phenomenological Analysis (IPA) approach, data were collected through in-depth interviews with five participants from diverse educational and professional backgrounds. The findings reveal that the effectiveness of AI interaction is strongly influenced by the clarity of prompt intentions, users’ ability to develop iterative and context-sensitive instructional communication strategies, and the contribution of visual literacy in improving the precision of visually oriented outputs. Participants with backgrounds in design and communication demonstrated greater capability in translating ideas into detailed prompts that aligned with expected outcomes. The study concludes that communication competence, rather than technical programming expertise, constitutes a key capability in vibecoding practices and highlights the importance of integrating AI communication literacy into communication education curricula.